PENGARUH PRODUK PROMOSI DAN PELAYANAN TERHADAP KEPUTUSAN NASABAH PEGADAIAN SYARI’AH PASAR MERDEKA DI SAMARINDA - Afandi, Amrulah; Fahleti, Widya Hana; Zainuddin, Muhammad (I-Con Media, 2023)
The Influence of Products, Promotions, and Services on Customer Decisions at the Merdeka Pawnshop Syari'ah Market in Samarinda. This study aims to determine the effect of product, promotion and service variables simultaneously on the decisions of Pegadaian Syariah Merdeka Market customers in Samarinda and want to know the effect of product, promotion and service variables partially on the decisions of Pegadaian Syariah Merdeka Market customers in Samarinda. The analytical tool used to analyze these variables is multiple regression. To test the proposed hypothesis is to use the f test and t test. the number of samples in this study were 123 customers. The research results obtained are that there is a simultaneous influence between product, promotion and service variables on the decisions of Pegadaian customers. The first hypothesis proposed is accepted because it is proven true. There is a partial influence between product variables on customer decisions, the second hypothesis proposed is accepted because it is proven true. There is a partial influence between promotion variables on customer decisions, the third hypothesis proposed is accepted because it is proven true. There is a partial influence between product variables on customer decisions, the fourth hypothesis proposed is accepted because it is proven true.